THE DETERMINATION OF FACTOR INFLUENCING MEDICATION ADHERENCE AMONG PATIENTS WITH SCHIZOPHRENIA: A QUALITATIVE STUDY - MERİÇ, Meltem; ERGÜN, Gül (Göbeklitepe Medical Science Journal, 2022)
Factors related to treatment adherence in patients with schizophrenia have always been key to the treatment of these patients. The aim of this study is to determination of treatment adherence and ıts influencing factors in patients with schizophrenia. This is a descriptive phenomenology study. The research was conducted with 15 patients, between October 2018 and January 2019. Participants in the research were selected by purposive sampling. Data collection was by the face-to-face interview technique. A personal information form and a semi-structured interview form were used to collect data. The mean age of the sample was 44.9 ± 7.2. 80% were male and 53.3% were secondery school graduates. As a result of the coding, 4 themes were determined. It is concluded that the continuation of community mental health centers schizophrenia patients contributes positively to their adaptation. It is important that determination of the affecting factors of treatment adherence by nurses and working with patient to improve treatment adherence.